2015
DOI: 10.1101/017129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How complexity originates: The evolution of animal eyes

Abstract: Learning how complex traits like eyes originate is fundamental for understanding evolution. Here, we first sketch historical perspectives on trait origins and argue that new technologies offer key new insights. Next, we articulate four open questions about trait origins. To address them, we define a research program to break complex traits into components and study the individual evolutionary histories of those parts. By doing so, we can learn when the parts came together and perhaps understand why they stayed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 186 publications
0
39
0
Order By: Relevance
“…Consistent with this hypothesis, Blanco‐Vive, Aliaga‐Guerrero, Canavate, Munoz‐Cueto, and Sanchez‐Vazquez () showed that the amount and wavelength of light influenced hatching, growth, and development rate in Senegal sole ( Sola senegalensis ) and Villamizar, Vera, Foulkes, and Sanchez‐Vazquez () found that the amount and the wavelength of light influenced the onset of locomotor activity in developing zebrafish. Non‐visual opsins might also induce a protective response to photo‐oxidative stress and DNA damage caused by exposure to light (Oakley & Speiser, ). Larval amphibians and fish are particularly susceptible because they are translucent/transparent.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, Blanco‐Vive, Aliaga‐Guerrero, Canavate, Munoz‐Cueto, and Sanchez‐Vazquez () showed that the amount and wavelength of light influenced hatching, growth, and development rate in Senegal sole ( Sola senegalensis ) and Villamizar, Vera, Foulkes, and Sanchez‐Vazquez () found that the amount and the wavelength of light influenced the onset of locomotor activity in developing zebrafish. Non‐visual opsins might also induce a protective response to photo‐oxidative stress and DNA damage caused by exposure to light (Oakley & Speiser, ). Larval amphibians and fish are particularly susceptible because they are translucent/transparent.…”
Section: Discussionmentioning
confidence: 99%
“…3; Suzuki et al, 2014). From a similar standpoint, the importance of such a component-based approach was discussed by taking the evolution of animal eyes as an example (Oakley and Speiser, 2015).…”
Section: Analyses: Evolutionary Processes and Pcmsmentioning
confidence: 99%
“…One of the newest debates -and the one most pertinent to vision in humans -is whether the opsins of animals were exapted from melatonin receptors [11,15,16]. Despite the intriguing possibility that a hormone receptor gained the ability sense light, we will not discuss this here, as opsin evolution has been thoroughly reviewed elsewhere [10,17]. Microbial photoreceptors, meanwhile, are rarely included in reviews of eye evolution, yet they have much to teach us about photosensory evolution.…”
Section: Eukaryotes Evolved Photoreceptors Multiple Times From Light-mentioning
confidence: 99%
“…Since the elucidation of lens crystallins, the conceptual usefulness of exaptation has broadened further, and is now a consideration in even more ancient features of DOI 10.1002/bies.201600266 photoreception [8]. This includes the Pax-6 master control genes that initiate eye development [9], as well as diverse phototransduction pathways in animals [10], and even the origins of opsins in animals [11]. Here we expand on this theme, mainly drawing on discoveries in microbial eukaryotes (protists), such as phytoplankton and unicellular fungi.…”
Section: Introductionmentioning
confidence: 99%